Spectrum of congenital heart disease in a tertiary care centre of Eastern India - Mahapatra, Anuspandana; Sarangi, Rachita; Mahapatra, Partha Pratim (International Journal of Contemporary Pediatrics, 2017)
Background: Congenital heart disease (CHD) is not an uncommon entity in our country. The prevalence of CHD is 9.3 per 1000 life birth in Asia which is found to be highest globally. Not much of Indian data is available particularly from this part of the country. So we conduct a retrospective study to know the spectrum of congenital heart disease in our set up. Methods: This is a retrospective hospital based study carried out over a period of 20 months (2015 March - 2016 November) where all suspected children (< 14 years) of CHD were subjected to echocardiographic study. The age, sex, clinical presentation and echo findings were well documented. Results: The total number CHD diagnosed were 231 and were more common among males (54.5%) with male to female ratio is 1.2:1. CHD were diagnosed more commonly between 1 month to 1 Year (40.25%). The commonest type of acyanotic CHD in our study was ventricular septal defect (VSD) (36.3%) and cyanotic CHD is tetralogy of Fallot (11.25%). The major clinical finding was a detection of a murmur (84.8%) followed by tachycardia (41.5%) and tachypnea (36.3%). Conclusions: In this era of most accurate diagnostic modalities, any clinical suspicion of congenital heart disease should be confirmed by echocardiography to hasten the diagnosis, timely management and prevention of complications.